Karakteristik Working Area di Atas Kapal Mini Purse Seine di Pelabuhan Perikanan Pantai Larangan Kabupaten Tegal - Mohammad Imron; Muhammad Dendy Alamul Huda; Yopi Novita (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
Mini purse seiner are the dominant vessels were operating in Tegal Regency and the number of these vessels have been increasing. These vessels at Larangan fishing port consist of 44 vessels of <10 GT and 37 vessels of ≥10 GT. Working activities on vessels <10 GT requiring 10 crew members, while vessels of ≥10 GT needs 15-20 crew members. Work accidents above the deck of the vessels have a high accident rate and are closely related to the value of theworking area. This research was intended with the aim of identifying activities and working area needs on the vessel by identifying the area of the used working area and formulating the adequacy of the work area for fishing activities. The sampling technique using a accidental sampling method with total sample is two to vessels <10 GT and three to vessels ≥10 GT . The data processing using mathematical calculations. Data analysis used descriptive analysis metode. The results of this study showed that the value of working area of vessels when setting conditions still far from sufficient area value. This conditions occurred because all crew gather in the same area when setting steps was conducted. The area mentioned which is on the left side of the ship when lowering the fishing gear, this will certainly increase the risk of work accidents.